Future horizons in the analysis of technical-tactical performance in women’s football: a mixed methods approach to the analysis of in-depth interviews with professional coaches and players - Iván-Baragaño, Iyán; Ardá, Antonio; Anguera, M. Teresa; Losada, José Luis; Maneiro, Rubén (Frontiers in Psychology, 2023)
Scientific knowledge about the criteria that determine success in women's football is beginning to develop. This study was carried out with the aim of detecting regularities in the offensive success in elite women's football, as well as carrying out an interrelational analysis of linked behaviors, based on in-depth interviews with professional coaches and players. Eight in-depth interviews were conducted with professional Spanish coaches and players. The interviews were analyzed by indirect observation from a process of "quantitizing", through the construction of an indirect observation ad hoc instrument. The segmentation of the transcription of the interviews was carried out in textual units, and the creation of a matrix of codes. Two types of analysis were performed: firstly, a lag sequential analysis (LSA) was performed and, then, a polar coordinates analysis (PCA), which allowed to find, respectively, a wide number of established communicative patterns with offensive performance in women's football, as well as an interrelational map between the established codes. The results obtained allowed us to suggest a statistically significant association between success in women's football and criteria such as the physical characteristics of a particular player, the individual action space, the duration of the attack, the type of dynamic start, individual and collective technical and tactical aspects, decision making and the type of attack used. Based on these results, the influence of these criteria on performance in women's soccer can be studied in future studies. In addition, with the aim of increasing the validity of these conclusions, new studies on this subject may be carried out following strategies such as the Delphi Method.